Contextual Influences on Child Feeding in Two South Asian Immigrant Groups - Karasz, Alison; Shiriti, Margia; DeSilva, Nilifa; Khurshid, Afrida; Bonuck, Karen; Ramachandran, Usha (International Journal of Child Health and Nutrition, 2020)
Child obesity is a major health disparity, with low-income communities bearing a disproportionate burden of disease. Although the powerful influence of socio-economic status on child diet and feeding practices is well established, its local contextual mechanisms are not necessarily well understood. This study used a qualitative comparative design to explore the socio-cultural context of child feeding ethnically similar but economically diverse immigrant families. Seventeen in-depth qualitative interviews conducted with affluent and low-income immigrant mothers from the South Asian subcontinent. We sought to explore potential contextual influences on maternal feeding practices, including: maternal beliefs and values, patterns of help and information seeking, family and household, and impacts of the chrono-system—the role of memory and life transitions. Our findings help to explain mechanisms underlying SES disparities in child obesity in this group, and maybe helpful in designing tailored interventions aimed at reducing these disparities.